Lingkungan Sekolah Membentuk Karakter Siswa: Studi Komparatif Sekolah Islam Terpadu dan Sekolah Umum di Nusa Tenggara Barat - Muzawir (STAI AL-AMIN, 2026)
Character education has become a strategic issue in the national education system. This study aims to analyze the role of the school environment in shaping students’ character and to compare Integrated Islamic Schools (Sekolah Islam Terpadu/SIT) and public schools in West Nusa Tenggara (NTB) based on Albert Bandura’s Social Learning Theory. This research employed a qualitative approach with a comparative study method. The research subjects involved 121 informants consisting of teachers, students, and parents from four schools. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that the school environment plays a significant role in students’ character formation. Integrated Islamic Schools demonstrate more structured and consistent value habituation, while public schools emphasize national and social values. These findings reinforce Bandura’s theory that character is formed through observation, imitation, and social reinforcement.